2016
DOI: 10.1016/j.ejr.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between serum leptin, cytokines, cartilage degradation and functional impact in obese knee osteoarthritis patients

Abstract: Aim of the work: The aim of the present work was to correlate between serum level of leptin, matrix metalloproteinase-13 (MMP13), interleukin-1b (IL1b), tumour necrosis factor (TNFa), nitric oxide (NO) and functional impact in obese patients with knee osteoarthritis (KOA).Patients and methods: The study included 84 obese patients suffering from primary KOA. The knees were examined; pain assessed by visual analogue scale (VAS) and Lequesne's index for functional impact calculated. Serum leptin, MMP13, IL1b, TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Obesity is a significant risk factor for knee osteoarthritis (OA) and also increases risk of OA in nonweight-bearing joints, leading Hussein and Sharara to suggest that mechanical factors alone may not explain the impact of obesity on knee OA. 46 Their study of 84 patients with obesity and knee OA implicates the hormone leptin, which was not only significantly correlated with BMI but was also shown to be significantly correlated with levels of specific cytokines (IL1b and TNFa) and certain metalloproteinases (MMP13), which enhance cartilage degradation.…”
Section: Obesity Comorbiditiesmentioning
confidence: 99%
“…Obesity is a significant risk factor for knee osteoarthritis (OA) and also increases risk of OA in nonweight-bearing joints, leading Hussein and Sharara to suggest that mechanical factors alone may not explain the impact of obesity on knee OA. 46 Their study of 84 patients with obesity and knee OA implicates the hormone leptin, which was not only significantly correlated with BMI but was also shown to be significantly correlated with levels of specific cytokines (IL1b and TNFa) and certain metalloproteinases (MMP13), which enhance cartilage degradation.…”
Section: Obesity Comorbiditiesmentioning
confidence: 99%
“…The characteristic of the age in this study showed the average age of the patient who had been diagnosed with OA genu was 63,6 years old with a range of 53-82 years old. The relationship between age with gender to the occurrence of OA was closely related, according to the statement of Felson, Roman-blas et al, Hussein, and Sharara, were the most diagnosed of OA was a female with age more than 50 years old (after menopause) because it was related to the role of hormones that affected cartilage metabolism [1,10,11]. The aging of the cartilage causes damage function and structure of chondrocytes thereby disrupting homeostasis and reducing the quality of the cartilage matrix [1,10,[12][13][14].…”
Section: A Characteristic Of Reasearch Subjectsmentioning
confidence: 99%
“…Osteoarthritis (OA) is expected to become more common with increase age and overweight populations. It is characterized by degradation of articular cartilage, osteophytes formation, sclerosis of subchondral bone, joint capsule alterations, destruction of extracellular matrix and synovitis [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%